'Terror & tension' psychophysiological suspense: defining a framework to measure cinematic suspense in 21st century horror films - Bound, Keith (2016)
The construction of suspenseful sequences has been a crucial component for filmmakers to engage the viewer, especially within the thriller and horror genres. This thesis takes a new approach to understanding cinematic suspense by creating a psychophysiological model to measure cinematic suspense and subsequently viewer experience. To date, film scholars and media psychologists have defined the process of suspense in terms of specific story case studies, rather than first independently identifying the components of suspense. Such theories become selective and open to subjective interpretation and have provided misinterpretations of the phenomenon of suspense (Friedrichsen, 1996: 329). Suspense then by existing definitions is not measurable and makes it hard to quantify any discussion of cinematic suspense in relation to viewer experience. Although film scholars and media psychologists recognise that the experience of suspense involves cognition, emotion and physiology, only media psychologists have carried out empirical studies with viewers. Even taking this into consideration there have only been a few psychophysiological studies about the experience of suspense (Kreibig, 2010: 408). Furthermore there is a methodological dilemma, with film scholars preferring a qualitative approach, often via film textual analysis, and media psychologists primarily taking a quantitative approach, analysing data sets using statistical models, which film scholars see as offering little contribution to the complexities of film analysis (Smith, M. 2013). The differences between these methodological approaches raise the question of whether we can gain a greater insight into viewers’ experiences of suspense by drawing elements from both research methods and identifying the most appropriate methods, procedures and techniques to defining cinematic suspense. One strategy for achieving this is to turn to the field of Human Computer Interaction (HCI) which often uses mixed methods approaches to resolve such interdisciplinary differences, especially in gaining a deeper insight into user/viewer experience of narrative trajectories (Benford et al. 2009).